2007
DOI: 10.1086/518640
|View full text |Cite
|
Sign up to set email alerts
|

Position‐Velocity Diagrams for the Maser Emission Coming from a Keplerian Ring

Abstract: We have studied the maser emission from a thin, planar, gaseous ring in Keplerian rotation around a central mass observed edge-on. The absorption coefficient within the ring is assumed to follow a power-law dependence on the distance from the central mass as ¼ 0 r Àq . We have calculated position-velocity diagrams for the most intense maser features, for different values of the exponent q. We have found that, depending on the value of q, these diagrams can be qualitatively different. The most intense maser emi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The linear position-velocity diagram in Figure 5 may be explained by an edge-on Keplerian rotating ring (e.g., Uscanga et al 2007), despite the nearly face-on geometry of the jet as shown in Motogi et al (2016). Such an apparently misaligned geometry might be possible, if the jet significantly bends within 100 au from the launching point.…”
Section: Origin Of the Velocity Gradientmentioning
confidence: 96%
“…The linear position-velocity diagram in Figure 5 may be explained by an edge-on Keplerian rotating ring (e.g., Uscanga et al 2007), despite the nearly face-on geometry of the jet as shown in Motogi et al (2016). Such an apparently misaligned geometry might be possible, if the jet significantly bends within 100 au from the launching point.…”
Section: Origin Of the Velocity Gradientmentioning
confidence: 96%
“…In particular, locating the position of emitters precisely is a critical point (e.g. Uscanga et al 2007). In order to check whether the method is "robust" enough to infer some reliable information about masses, we generated a sample of N points {̟ i ,μ i }, obeying exactly Eq.…”
Section: Uncertainties and Data Dispersionmentioning
confidence: 99%
“…We subtracted the ring systemic velocity of 476 km s −1 from the observed LSR velocity of the maser spots in order to compare the observed PV diagram with the modelled one. The positions and velocities are in units of the outer radius of the ring (8 mas) and the rotation velocity at the outer edge of the ring (770 km s −1 ), respectively (Uscanga et al 2007).…”
Section: Model and Resultsmentioning
confidence: 99%
“…The systemic masers lie within a narrow range of radii, on the near side inner edge of the ring, while the high-velocity masers are located near the ring diameter. Previously, Watson & Wallin (1994) showed that the maser emission from a rapidly rotating, thin Keplerian ring viewed edge-on can reproduce the general features of the observed 22 GHz radiation of this galaxy. However, their assumption of a uniform absorption coefficient within the amplifying ring results in a PV diagram for the most intense masers that is qualitatively different from the observed one.…”
Section: Introductionmentioning
confidence: 90%